A cross sectional study on menstrual hygiene of adolescent girls in rural field practice area of Kalaburagi, Karnataka, India - Chapparbandi, Shweta R.; Nigudgi, S. R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescents make nearly one tenth of Indian population and form a crucial segment of the society. A large variety of morbidities such as nutritional deficiency disorders (stunting, wasting), menstrual disorders, etc. prevail among them. Menstruation is generally considered as unclean in the Indian society. Isolation of the menstruating girls and restrictions being imposed on them in the family, have reinforced a negative attitude towards this phenomenon. There is a substantial lacuna in the knowledge about menstruation among adolescent girls. Adolescent girls have incomplete and inaccurate information about the menstrual physiology and hygiene. Good hygienic practices such as the use of sanitary pads and adequate washing of the genital area are essential during menstruation. Methods: A cross-sectional study was carried out from January to December 2012. House to house survey was conducted; a pre-structured and pre-tested questionnaire was administered to all the adolescent girls of 10-19 years in the study area. Results: Majority of girls 121 (38.05%) were in high school; Out of 318 adolescent girls, 200 (62.89%) had attained menarche when they were 13-14 years old; Among 200 girls, majority 138(69%) use piece of cloth and 62 (31%) use sanitary pad as sanitary protection during menstruation. There was a significant association between usage of sanitary protection (cloth/pad) and education of adolescent girls (p<0.05). Conclusions: Health education programs regarding menstrual hygiene are necessary in rural areas and social marketing of sanitary napkin should be promoted to avoid use of unhygienic sanitary napkins.